Epidemiologia e aspectos clínicos da distonia tarefa específica em músicos no Brasil - Moura, Rita de Cassia dos Reis [UNIFESP] (2017)
Background: Focal dystonia among musicians is a task-specific dystonia triggered by a specific motor movement. Its primary cause is unknown. Musician's dystonia is a task- specific focal dystonia that can occur in any part of the body, most commonly on the face, neck muscles and upper limbs. Its frequency among the Brazilian population is unknown. Objectives: To evaluate the clinical characteristics and frequency of task specific dystonia in musicians among Brazilian musicians. Methods: To identify individuals with dystonia, we visited orchestras and music schools in 19 Brazilian cities between March 2013 and March 2015, providing information about task-specific dystonia in musicians. Musicians were invited to answer the questionnaire, and those with a possible neurological dysfunction associated with musical performance were recorded by video while playing the instrument. It was also applied the assessment of anxiety states and the severity of dystonia Results: In total, 2233 questionnaires were completed, with 72 subjects recorded on video in specific tasks. In total, 49 individuals were diagnosed with task specific focal dystonia in musicians (mean age 36.4 (±) 12.2 years 92% male). The instruments most associated with task specific dystonia in musicians was the guitar acoustic and the wind brass instruments. Conclusion: Our results suggest that the frequency of focal dystonia among musicians in Brazil is 2.5%, it can initially appear around 30 years old and is mostly associated with males, professional musicians who play classical concert music and in people who perform other activities using their upper limbs. Musculoskeletal injuries appear prior to the onset of dystonia. Cultural and regional differences are indicative factors to determine predictive instruments and affected areas. Task specific dystonia in musicians is a condition that deserves further attention from musicians, teachers and health professionals.